Intensive care unit nurses’ perceived Barriers to Optimal Pain management: A cross-sectional study in Tanzania - Banafsheh Ghorbani; Joel Simbeye; Majed Dehghani; Fatemeh Bahramnezhad (Journal of Research Development in Nursing and Midwifery, 2025)
Background: Inadequate pain management among critically ill nonverbal patients in ICUs is a significant public health issue that can lead to prolonged mechanical ventilation and poor quality of life. Critical care nurses play a vital role in mediating pain management, and identifying barriers they face is essential for developing effective pain relief policies. This study aimed to assess nurses' perceived barriers to pain management in ICUs. Methods: The study employed a cross-sectional design, adhering to STROBE reporting guidelines, and was conducted from January to May 2022 across four national referral hospitals in Tanzania, including university-affiliated and public hospitals. It utilized the Eastern Cooperative Oncology Group (ECOG) barrier tool to assess critical care nurses' perceived barriers to pain management in the ICU, with data analyzed using the Kruskal-Wallis test. A total of 202 nurses were recruited through census sampling. Data collection involved demographic questionnaires alongside the ECOG barrier tool to evaluate the challenges faced by nurses in managing pain effectively. Results: The findings revealed that there were perceived nurse barriers related to medical staff and patients with the overall mean 4.57± 1.25 and 3.90±1.17 respectively.  ICU nurses did not perceive barriers related to the healthcare system with an overall mean 2.33±0.78. Conclusion: Critical care nurses perceive barriers related to medical staff and patients as significant obstacles to effective pain management in ICUs. Intensive training on diagnosis and assessment, along with the use of tools like the Behavioral Pain Scale (BPS) and Critical Care Pain Observation Tool (CPOT), is essential for improving outcomes. Additionally, integrating patients' cultural backgrounds into pain assessments is crucial for effective management.